PENGARUH JUMLAH SAHAM BEREDAR, IFR, TINGKAT PENGUNGKAPAN INFORMASI WEBSITE DAN HARGA SAHAM PENUTUPAN TERHADAP FREKUENSI PERDAGANGAN SAHAM PERUSAHAAN (Studi pada Perusahaan yang Terdapat pada Indeks Kompas 100 Februari-Juli 2015) - Elta, Ledina; Kamal, Mustofa (Diponegoro Journal of Management, 2016)
The capital market unite the company and investors. In determining which companies to be selected, investors carry out several analyzes, including analyze the price and frequency stock trading in the past to estimate the frequency in the future. Frequency trading is influenced by several factors, including the number of shares traded, the fundamental factors, the disclosure of information, and stock prices. Meanwhile, technology (internet) develop very fast and influenced the form of financial statements via the internet or the website called Internet Financial Reporting (IFR), while for non-financial information , companies use websites to reduce asymmetry information about the company. This study aims to determine the effect of the number of traded shares, IFR, the level of website disclosure, and the closing stock price toward the frequency of company’s shares trading.The data used in this study is a cross section data. This study uses the 94 companies that included in the  KOMPAS100  index period from February to July 2015, have a website and apply IFR. Linear regression is used to determine the effect of the number of traded shares, IFR, the level of website disclosure, and the stock price toward the frequency of company’s shares trading.The results of this study indicate that according to the F test, the number of outstanding shares, IFR, the level of disclosure website, and stock prices affect the frequency trading (sig. 0.000), while according to the t test, partially only the number of shares outstanding and the stock price a positive and significant effect (with sig. 0.000), while IFR (sig. 0.732) and the level of information disclosure website (sig 0.805) did not significantly affect the company's shares trading frequency. Meanwhile, according to determination test, the number of outstanding shares, IFR, the level of information disclosure website and the closing share price affect the frequency of the company's shares trading amounted to 54.9%.